2013
DOI: 10.1136/bmjopen-2013-002881
|View full text |Cite
|
Sign up to set email alerts
|

Effects of centrally acting ACE inhibitors on the rate of cognitive decline in dementia

Abstract: ObjectivesThere is growing evidence that antihypertensive agents, particularly centrally acting ACE inhibitors (CACE-Is), which cross the blood–brain barrier, are associated with a reduced rate of cognitive decline. Given this, we compared the rates of cognitive decline in clinic patients with dementia receiving CACE-Is (CACE-I) with those not currently treated with CACE-Is (NoCACE-I), and with those who started CACE-Is, during their first 6 months of treatment (NewCACE-I).DesignObservational case–control stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
52
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 62 publications
(32 reference statements)
0
52
1
4
Order By: Relevance
“…Studies are few, with little convincing evidence supporting benefit, harm, and safety for any agent, suggesting that providers must use the same judgment as in the non-demented [124]. Centrally acting ACEIs may be associated with a reduced rate of cognitive decline [125]. With both hypertension and dementia being common, there is uncertainty over whether the benefit in prevention of cognitive impairment is secondary to a lowering of BP or is a specific drug class benefit [97].…”
Section: Dementiamentioning
confidence: 99%
“…Studies are few, with little convincing evidence supporting benefit, harm, and safety for any agent, suggesting that providers must use the same judgment as in the non-demented [124]. Centrally acting ACEIs may be associated with a reduced rate of cognitive decline [125]. With both hypertension and dementia being common, there is uncertainty over whether the benefit in prevention of cognitive impairment is secondary to a lowering of BP or is a specific drug class benefit [97].…”
Section: Dementiamentioning
confidence: 99%
“…Relationships between blood pressure lowering and dementia risk are less well understood [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22], particularly in very old age [3]. Systematic reviews [10][11][12], clinical trials [13,14,19] and observational studies [15][16][17][18][20][21][22] variably report antihypertensive drug use as associated with decreased risk of dementia/cognitive decline [14][15][16][17][18][19][20][21], increased risk [22], or no impact [10][11][12][13]. The majority of double-blind randomized placebo controlled trials show no relationships.…”
mentioning
confidence: 99%
“…However, two trials in the young old (below age 70) report reductions in incident dementia: from an angiotensin-converting enzyme-inhibitor (ACE-I) plus optional diuretic, but only in those with prior stroke/transient ischaemic attack and concurrent stroke, mean age 64 years [14]; and from calcium channel blockers (CCB), mean age 69.9 years [19,20]. Observational literature shows beta-blockers, CCBs, ACE-I and diuretics as associated with some positive cognitive outcomes, again mostly in the younger old (mean age at baseline ranged from $68 to 78 years) [15][16][17][18]. Evidence is strongest for CCBs with the suggestion that their impact may be independent of blood pressure lowering [11,12].…”
mentioning
confidence: 99%
“…Several studies suggested an involvement of the renin-angiotensin system (RAS) and ACE on cognitive performance, as improved cognition and delayed dementia progression were associated with the use of ACE inhibitors (Ohrui et al, 2004;Kehoe and Wilcock, 2007;Yamada et al, 2011;Gao et al, 2013). Thus, considering that cognitive impairments are central features of SCZ (Kahn and Keefe, 2013), these results might direct future studies on the ACE roles on cognition in SCZ patients.…”
Section: Discussionmentioning
confidence: 97%